KORELASI FAKTOR SUAMI TERHADAP MINAT PENGGUNAAN ALAT KONTRASEPSI INTRA UTERINE DEVICE - Yulita, Hendra; Utama, Risma Putri; Mahendika, Devin; Indriani, Farihah (Ensiklopedia of Journal, 2025)
Abstract: IUD (Intrauterine Device) is one type of Long Term Contraceptive Method (MKJP) that is highly recommended by the government to use. Based on an initial survey conducted in the working area of the Sungai Bulian Health Center, it is known that the low use of the IUD is because mothers feel embarrassed and afraid of the installation of the IUD. Mothers feel embarrassed because the installation of the IUD is done through the vagina. Mothers feel afraid because they are worried that health workers are not skilled in installing IUDs that can cause side effects as well as because the IUD is inserted in the uterus. Husband support was also not obtained by the respondents interviewed, including the husband did not participate in the selection of contraceptives, did not take the mother for the installation of contraceptives. The purpose of the study was to determine the correlation of husband factors with interest in the use of Intra Uterine Device contraceptives. The research design used in this study was cross sectional. The research was conducted in the Working Area of the Sungai Bulian Health Center. The research was conducted in November 2023. The population is active family planning acceptors in the Sungai Bulian Health Center working area totaling 453 people. The sample amounted to 74 people. The sampling technique used Simple Random Sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed a relationship between husband's income (p value: 0.044) and husband's support (p value: 0.018) on interest in using the IUD. It is recommended for Puskesmas to be more active in providing health information to improve IEC to married couples who want to use family planning, especially the IUD, and health workers also provide information to PUS to bring their husbands to participate in socialization so that husbands can support their wives to use family planning, especially the IUD.Keywords: Husband Support, Intra Uterine Device, Income.